Toward an Integral Practice of Architecture (Birkhäuser, 2014)
The integration of functions, technology and aesthetic quality is the architect’s core qualification. In this book, the partners of Richter & Dahl Rocha provide a detailed and comprehensive account of today’s state of the art of architectural design. Offering the knowledge of 20 years of high-class practice to the architectural community, the professional value is confirmed by RDRs achievements, including the EPFL Swiss Tech Convention Center.